2022
DOI: 10.1139/facets-2021-0181
|View full text |Cite
|
Sign up to set email alerts
|

Protecting expert advice for the public: promoting safety and improved communications

Abstract: The drivers of the harassment and intimidation of researchers are complex, widespread, and global in their reach and were being studied across many disciplines even before COVID-19. This policy briefing reviews some of the scholarship on this wide-ranging problem but focuses on what can be done to help ensure that Canadians fully benefit from the work of Canada’s researchers while also preserving the security and safety of those researchers. It identifies policies and actions that can be implemented in the nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…These fears are concerning as they can manifest themselves as selfcensorship, thus preventing sharing of information to the public and policy-makers (Bar-Tal 2017; Driscoll et al 2021;Robertson et al 2023). Our finding of women-identifying researchers reporting more fear of media is consistent with previous research (Brescoll 2011;Funk and Parker 2018;Donegan 2022;Wright et al 2022), which has found that women are less likely to speak to the media due to fears of backlash and more likely to be at the receiving end of discriminatory behaviours and action. One respondent in our study further supported this theory in their open text response: "Seeing how women are treated on social media, I am not interested in receiving that type of trolling so [I] stay away from politics or adding commentary on social media" (participant ID 346, Q30).…”
Section: Gendersupporting
confidence: 88%
See 1 more Smart Citation
“…These fears are concerning as they can manifest themselves as selfcensorship, thus preventing sharing of information to the public and policy-makers (Bar-Tal 2017; Driscoll et al 2021;Robertson et al 2023). Our finding of women-identifying researchers reporting more fear of media is consistent with previous research (Brescoll 2011;Funk and Parker 2018;Donegan 2022;Wright et al 2022), which has found that women are less likely to speak to the media due to fears of backlash and more likely to be at the receiving end of discriminatory behaviours and action. One respondent in our study further supported this theory in their open text response: "Seeing how women are treated on social media, I am not interested in receiving that type of trolling so [I] stay away from politics or adding commentary on social media" (participant ID 346, Q30).…”
Section: Gendersupporting
confidence: 88%
“…Finally, as our survey found that over 50% of respondents experienced fear of media and many of these individuals being from marginalized groups, we echo Robertson et al (2023) in recommending increasing protection of researchers when they interact with both traditional and social media. Drawing from suggestions by Wright et al (2022), we recommend that institutions who employ researchers in the environmental studies and sciences (1) create training modules for researchers regarding safety and effectiveness in knowledge mobilization activities, with a section or specific focus for researchers from marginalized groups and (2) foster a readily accessible policy and action plan in place to support researchers who are significantly harassed, threatened, or intimidated because of their research, social identity, or public-facing work. In Canada, the federal government might consider collaborating with the Canada Research Coordinating Committee and other relevant agencies to coordinate a nationwide approach to gathering information about online threats and harassment across sectors.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…14 In particular, online harassment of scientists was a common problem even in the prepandemic era, but it acquired far more visibility during the COVID-19 pandemic. [15][16][17][18] Bullying and harassment in academic circles is very frequent: a national Swedish survey found that 7% of students and employees across 38 institutions of higher learning had experienced bullying or harassment in the previous 12 months, 19 and a Wellcome 2020 report on What Researchers Think About the Culture they Work In found that 61% of researchers had experienced bullying or harassment, but only 37% felt that they could speak about it. 20…”
Section: Current Epidemiology Of Obsessive Criticism and Bullying In ...mentioning
confidence: 99%
“…However, anecdotally it is likely that obsessive contributions by other scientists (especially those with strong social media and media presence) may be particularly incendiary, since they also provide to non‐specialist attackers “science‐based” justification to enhance cancel campaigns 14 . In particular, online harassment of scientists was a common problem even in the pre‐pandemic era, but it acquired far more visibility during the COVID‐19 pandemic 15–18 …”
Section: Current Epidemiology Of Obsessive Criticism and Bullying In ...mentioning
confidence: 99%
See 1 more Smart Citation